In vitro susceptibility of OXA-48, NDM, VIM and IMP enzyme- producing Klebsiella spp. and Escherichia coli to fosfomycin - Selay Demirci-Duarte; Tugce Unalan-Altintop; Zeynep Gulay; Ayse Nur Sari Kaygisiz; Asli Cakar; Deniz Gur (Journal of Infection in Developing Countries)
Introduction: Infections caused by Carbapenemase-producing Enterobacterales (CPE) are an important public health issue. Intravenous fosfomycin can be considered as an alternative for the treatment of serious infections caused by CPE. In this study, in vitro activity of fosfomycin was investigated among CPE isolates.